Composition of essential oil peppermint cultivated with methanolic extract of Leonurus sibiricus L. leaves - Bufalo, Jennifer [UNESP]; Rolim de Almeida, Luiz Fernando [UNESP]; Ribeiro Vieira, Maria Aparecida; Mayo Marques, Mrcia Ortiz; Fernandes Boaro, Carmen Silvia [UNESP] (Taylor & Francis Inc, 2014)
The invasive plant Leonurus sibiricus L. is known for the production of terpenoids and phenolic substances that exert allelopathic effects. The aim of this study was to investigate the effects of different concentrations of an L. sibiricus extract on the chemical composition of Mentha x piperita L. essential oils cultivated in a nutrient solution. The methanolic extract from L. sibiricus was tested at three different concentrations, 25, 50 or 100 mg/L, in hydroponically grown M. x piperita. The chemical compositions of the essential oils from the M. x piperita plant were evaluated at different times. The results showed that at all concentrations levels, menthol was the major component of the essential oil, comprising 35.2% (average percentage) of the oil components. Menthol and menthyl acetate showed some interesting divergent patterns; the presence of menthol was higher in the plants cultivated with 25 mg/L of the methanolic extract of L. sibiricus leaves, and the presence of menthyl acetate correlated with cultivation of the plants in 50 and 100 mg/L of the extract. The concentration of the methanolic extract of L. sibiricus leaves that was applied to the M. x piperita plants influenced the levels of the components in the essential oil.
Keywords: essential oil; methanolic extract; Mentha x piperita; menthol